Trainer CCTV Sebagai Media Pembelajaran Peralatan Pengamatan Keamanan - Bayu Purbo Wartoyo; Musri Kona; Saptandri Widiyanto (Politeknik Penerbangan Makassar, 2022)
In the Air Navigation Technology study program at Aviation Polytechnic of Makassar, there is a Security Observation Equipment course. This course studies airport security equipment to support aviation safety and security with one of the equipment that will be taught is CCTV. Aviation Polytechnic of Makassar plans to make a CCTV trainer to facilitate learning about CCTV and its installation in the Security Observation Equipment course. In this research, the first step to be carried out is to design a CCTV trainer that will be used in the course practicum. Furthermore, the second stage is the stage of assembling the CCTV trainer. After the CCTV installation is complete, the next step is to test the system to find out the system is running as it should. From this research, the authors were able to design a CCTV trainer using several types of CCTV, NVR, and Switch to be displayed on the monitor. In addition, with this research, the knowledge and abilities of the cadets of the Air Navigation Engineering, Makassar Aviation Polytechnic in the Security Observation Equipment course, have increased from the previous 21.2% and 37.9% to 43.9% and 48.5% in the category very good.